An Analysis of the Issues and Prospects of the Library Automation in the Mizoram Colleges: A comprehensive analysis of library automation in Mizoram college libraries (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper discusses the importance of Library Automation and highlights the areas, factors and benefits of library automation. It also brings out problems as well as the present condition and future prospects of library automation of College libraries in Mizoram.